The new approach to environmental auditing and environmental risks in M&A transactions - Huertas del Pino Cavero, Luis Felipe (2023)
In this paper the author seeks to provide detailed information on the basis of the new approach to environmental auditing carried out by the Organismo de Evaluación y Fiscalización Ambiental. This audit concerns all those targets that require or have a specific environmental certification. When these companies are part of M&A transactions, buyers or interested parties must carry out the due diligence with special attention to the compliance regarding environmental regulations, since it is currently an aspect of high regulation and potential fines with high amounts. The author emphasizes that if the buyer does not wish to be affected in the future, he should corroborate the cross- cutting information provided by the Administrative Law with the appropriate specialists and tools.